An overview of adolescents sexual and reproductive health services provision in Malaysia - Abdul Hamid, Siti Hazariah; Callery, Peter; Fallon, Debbie (Taylor & Francis Online, 2020)
Safer sex provision, including contraception information and services, should be made available to adolescents regardless of their marital status in strategies to reduce the incidence of unintended teenage pregnancies and the spread of STIs. In Malaysia, this information is still not being delivered formally to adolescents even though unintended teenage pregnancies and the practice of “baby dumping” are serious public health issues. The aims of this article are to describe the Malaysian context in terms of the need for comprehensive sexual and reproductive health information and treatment for unmarried adolescents. The article presents the key aspects of Malaysian society and the potential influence on the provision and delivery of sexual and reproductive health information and treatment to unmarried Malaysian adolescents that can be a reference for healthcare professionals especially school health nurses. The article also describes the establishment of sheltered homes, baby hatches and unregulated adoption processes as the initiatives being taken to address the issue of unintended teenage pregnancies. This article suggests that the policy and laws that require parental consent for accessing the services need to be reviewed and revised to ensure that specific services are available to adolescents in a safe environment that maintains confidentiality.